Mental Health, Climate Change, and Sustainable Public Health Action: A Scoping Review - Eduardo Chierrito; Suélen Manoel Favero; Mário Henrique da Mata Martins; Flávia Aparecida Reitz Cardoso; Rute Grossi-Milani (International Journal of Environmental Research and Public Health, 2026)
Background: Carbon-based energy systems drive climate change with growing pressure on public health, yet research on mental health, climate change, and carbon-intensive industries remains fragmented. Objective: This scoping review mapped how mental health outcomes of climate change relate to the carbon-based matrix, identifying conceptual approaches, methodological trends, and research gaps aligned with planetary health and the SDGs. Methods: This review was conducted following the Joanna Briggs Institute (JBI) and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines, with searches in PubMed, Web of Science, and PsycINFO. Results: From 232 records, 38 studies (2015–2025) were included across six clusters: eco-anxiety and distress (n = 14); extreme events and mental disorders (n = 9); air pollution and neuropsychological outcomes (n = 7); environmental justice and vulnerable populations (n = 10); green spaces and resilience (n = 6); and public policy and sustainable responses (n = 7). The carbon-based matrix was proximally linked to mental health in studies on air pollution and extractivism, and served as context in studies on extreme climate events, food insecurity, and climate uncertainty. Conclusions: An equitable transition away from carbon-intensive systems is a public health priority, with co-benefits for mental well-being aligned with the SDGs.